2019
DOI: 10.3389/fpls.2019.00742
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Physiological and Anatomical Mechanisms of Adaptation of Callistemon citrinus and Viburnum lucidum to NaCl and CaCl2 Salinization

Abstract: Callistemon citrinus and Viburnum lucidum are appreciated and widespread ornamental shrubs for their abundant flowering and/or brilliant foliage. The intrinsic tolerance to drought/salinity supports their use in urban areas and in xeriscaping. Despite adaptive responses of these ornamental species to sodium chloride (NaCl) have been extensively explored, little is known on the effects of other salt solution, yet iso-osmotic, on their growth, mineral composition and metabolism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 91 publications
3
33
1
Order By: Relevance
“…The effectiveness of cluster heat map analysis for simultaneously analyzing and interpreting multiple morpho-functional traits has been reported previously in a series of research papers [4,52,60]. This was the case in the current study, since this analysis has introduced important information on the differences between all treatments.…”
Section: Discussionsupporting
confidence: 59%
“…The effectiveness of cluster heat map analysis for simultaneously analyzing and interpreting multiple morpho-functional traits has been reported previously in a series of research papers [4,52,60]. This was the case in the current study, since this analysis has introduced important information on the differences between all treatments.…”
Section: Discussionsupporting
confidence: 59%
“…Shoot dry weight of Coleus blumei (coleus) treated with saline solution reduced when NaCl concentration increased from 0 to 60 mM (Ibrahim et al, 1990). Viburnum lucidum watered with 80 mM NaCl or 53.3 mM calcium chloride (CaCl 2 ) had a 28% reduction in shoot dry weight, but there was no significant change in the root dry weight compared with no salt treatment (Cirillo et al, 2019). When the salinity level of irrigation water increased to 200 mM NaCl (20.5 dS • m -1 ), the shoot and root dry weight of V. lucidum dropped by 37% and 29%, respectively, compared with the control (1.6 dS • m -1 ) (Cassaniti et al, 2009).…”
mentioning
confidence: 99%
“…Plant shoot growth is more sensitive to salinity stress than root growth, and an increased root-to-shoot (R/S) ratio is expected in response to salinity stress (Hanin et al, 2016). Cirillo et al (2019) determined that the R/S ratio increased from 0.49 to 0.61 in V. lucidum and from 0.37 to 0.46 in C. citrinus when the EC of irrigation water increased from 2.0 to 11.0 dS • m -1 . Acosta-Motos et al (2015) also observed an increasing R/S ratio in Myrtus communis (common myrtle) plants irrigated with NaCl solution at an EC of 8.0 dS • m -1 for 1 month.…”
mentioning
confidence: 99%
“…The species is considered as a low water-use plant [28,29] and is able to grow in regions with mild winters [30].Both species are widespread in the Mediterranean area of Italy, in gardens and green areas, because of their ornamental value and adaptability to many environmental conditions. Different studies were carried out on Viburnum to investigate on salt stress response [28,31], but little information is available in terms of growth parameters, photosynthetic efficiency, leaf functional anatomical traits in drought stress conditions.These two species were chosen on the basis of our previous studies [32]; Polygala myrtifolia L. and Viburnum tinus L. 'Lucidum' were found, respectively, to be moderately sensitive and sensitive to salinity. Since salinity and drought stresses share important adaptation strategies, this work was carried out to verify if unavailability of water activates the same adaptation strategy observed under salinity stress.…”
mentioning
confidence: 99%
“…Both species are widespread in the Mediterranean area of Italy, in gardens and green areas, because of their ornamental value and adaptability to many environmental conditions. Different studies were carried out on Viburnum to investigate on salt stress response [28,31], but little information is available in terms of growth parameters, photosynthetic efficiency, leaf functional anatomical traits in drought stress conditions.…”
mentioning
confidence: 99%